(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the mechanisms and strategies for fostering an active investment climate in rural areas. It examines the challenges faced by rural economies, analyzes existing literature on rural investment, proposes methods for improvement, presents empirical evidence of successful interventions, and concludes with recommendations for policymakers and stakeholders.